Impact of Artificial Intelligence on Employee Development at Basrah University - Ihsan Abdulsahib Noor, Nadia; Nassreddine, Ghalia; Younis, Jouman (Journal of Techniques, 2023)
Employees are the leading resource of any company because they are the base of a strong and long-running organization. Their performance affects the overall evolution of the organization. Thus, modern companies have started spending an enormous amount on employee development. It is an essential process for employees and organizations. Companies have started using recent technology in employee development to make this process more productive. Artificial Intelligence is a branch of computer science. It is based on the concept of imitation the human intellectual functioning. This research studies the impact of artificial intelligence on employee development. A descriptive analytical methodology is used. Artificial Intelligence is considered an independent variable. However, the dependent variable was Employee development with three dimensions (Skills, engagement, and performance). Basrah University in Iraq was taken as a sample. Consequently, a questionnaire of 24 questions is built and distributed to Basrah University employees. The collected answers were examined using SPSS. The result shows a significant impact between Artificial Intelligence applications and employee development.